2021
DOI: 10.1111/ncn3.12556
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of headaches in primary brain calcification in Japan

Abstract: Primary brain calcification (PBC) is also known as Fahr's disease, idiopathic basal ganglia calcification (IBGC), and primary familial brain calcification (PFBC). PBC is a rare neurodegenerative disorder characterized by bilateral calcification in the basal ganglia, cerebellar dentate nuclei, and thalami among others. Some of the patients, especially those with familial PBC, are found to have causative genes. Some PBC patients are asymptomatic, but for those with symptoms, their clinical manifestations widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In contrast, in six patients with the SLC20A2 variants that Batla reported in 2017, it was said that "headaches are relieved by oral medication, so it was not necessary to talk to a doctor about them [19]. Very recently, we have also showed that patients with the PDGFB variant have a tendency for a higher frequency of headaches [20]. The headaches in PBC may be the secondary headaches caused by the dysfunction of the blood-brain-barrier.…”
Section: Experiences Of the Patients Who Were Told They Suffer From A...mentioning
confidence: 92%
“…In contrast, in six patients with the SLC20A2 variants that Batla reported in 2017, it was said that "headaches are relieved by oral medication, so it was not necessary to talk to a doctor about them [19]. Very recently, we have also showed that patients with the PDGFB variant have a tendency for a higher frequency of headaches [20]. The headaches in PBC may be the secondary headaches caused by the dysfunction of the blood-brain-barrier.…”
Section: Experiences Of the Patients Who Were Told They Suffer From A...mentioning
confidence: 92%